HYDROTHERMAL EXPERIMENTS ON ALTERATION OF CA-AL-RICH INCLUSIONS (CAIS) IN CARBONACEOUS CHONDRITES: IMPLICATION FOR AQUEOUS ALTERATION IN PARENT ASTEROIDS - RESULTS OF EQ3/6 COMPUTER SIMULATION - Nomura K.; Miyamoto M. (My University, 1998)
Carbonaceous chondrites contain Ca-Al-rich inclusions (CAIs) which consist mainly of refractory minerals including gehlenite, spinel, perovskite, and hibonite which are predicted to be the first phases formed from early solar nebula on the basis of thermodynamic calculations. However, many CAIs contain secondary minerals such as nepheline, calcite, and phyllosilicates. The formation process of secondary minerals in CAIs is still controversial whether they were produced by the reaction with solar nebula or by aqueous alteration in parent asteroids. We performed hydrothermal experiments on gehlenite, spinel, and diopside which are common in CAIs in carbonaceous chondrites to study aqueous alteration in parent asteroids. Mixtures of gehlenite with SiO2 and/or Al2O3 and those of SiO2 with Al2O3 were also employed to study products of these systems which have a close relationship to crystallization of secondary minerals in CAIs in fluid in parent asteroids. Hydrogrossular, calcite, and amorphous Al-Si were obtained from gehlenite by hydrothermal experiments, whereas both spinel and diopside escaped alteration, suggesting that gehlenite is the weakest mineral among these refractory minerals against alteration. This result is consistent with observation of CAIs. Analcime, nepheline hydrate, and tobermorite were obtained from the runs for mixtures of gehlenite with SiO2, whereas the products from mixtures of Al2O3 with SiO2 were analcime, nepheline hydrate, and hydrosodalite. These results suggest that the alteration process of gehlenite is as follows: (1) Gehlenite was dissolved by fluid in chondrite parent asteroids to release Ca, Al, and Si from the surface. (2) CO32- in fluid reacted with Ca to crystallize calcite. (3) Na, Al, and Si in fluid crystallized nepheline hydrate, hydrosodalite, and/or analcime. (4) Ca, Al, and Si in fluid crystallized hydrogrossular without CO32-, and excess Ca and Si crystallized Ca-Si hydrate such as tobermorite. Heating experiments on several minerals obtained through hydrothermal experiments were also performed to study thermal metamorphism in parent asteroids. Hydrogrossular was converted into hydrogrossular with a lower H2O content, and analcime and nepheline hydrate were converted into nepheline. Tobermorite is known to be converted into wollastonite with increasing temperature. The results of experimental studies suggest that most secondary minerals found in CAIs in carbonaceous chondrites were produced from gehlenite by aqueous alteration and the subsequent thermal metamorphism in parent asteroids.